Stylometry without Words: Analyzing John Milton’s Grammatical Style - Quamen, Harvey (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2021)
In this article, Harvey Quamen investigates the structures—syntax, grammar, unconscious multilingualisms, hypotaxis, parataxis, punctuation, orthography, archaic words and spellings, ambiguous antecedents, and even simple errors—that support Milton’s language. Quamen demonstrates how contemporary computational methods can go beyond word frequency counts to assist us in learning more about Milton’s literary style, while showing us that the history of computational analysis in Milton studies is surprisingly long. He is meticulous in the methodology he uses, which he describes clearly and carefully in this article; and he concludes with a series of recommendations designed to align the interests of textual scholars and digital humanists.